AUTONOMOUS VEHICLE: SMART RC CAR - AHMAD F AROK, INT AN SHAKIRA (Universiti Teknologi Petronas, 2005)
The objective of this report is to build a prototype of an autonomous vehicle that can operate mostly on its own to get from a designated starting point to a designated destination. The basis of the prototype was a remote controlled (RC) connected to a personal computer. Communication between the RC car and the PC were achieved via two FM transmitter-receiver pairs. The intelligent part (car moving autonomously) was progranuned in the Visual Basic program with a fundamental usage of fuzzy logic. The software can control the basic movement of the car such as moving forward, turning and stopping. Obstacle avoidance was coded with the aid of obstacle sensors fitted to the front end of the car. The software was able to compute the distance traveled by counting the revolution of one of the wheels with the use of an Infrared (IR) sensor. The car was able to move from point A to point B through a pre-determined route while avoiding obstacles placed randomly along the route. This project is an alternative for inventing a 'smart' car which can travel on the road without the need of human control. An application from the project is a "Mobile Security Car" where the car runs on a pre-determine route to monitor an area with a camera attach on it. At the end of this report, conclusion and recommendations are made to summarize up the overall project progress.